Primary sclerosing cholangitis is associated with autoreactive IgA antibodies against biliary epithelial cells. (June 2013) - Berglin, Lena; Björkström, Niklas K.; Bergquist, Annika
Abstract Objective. Primary sclerosing cholangitis (PSC) is a chronic liver disease characterized by progressive destruction of the biliary tract system. Autoimmune reactions have been suggested to play a role in the etiology and pathogenesis of PSC, and a large number of different autoantibodies have been reported in PSC patients. However, the role of IgA, being the dominant immunoglobulin in bile and transported there via biliary epithelial cells, is still incompletely understood in PSC. The aim of this study was to evaluate the presence of autoreactive IgA in PSC patients. Material and methods. Cultures of biliary epithelial cells from healthy human liver tissue were established. Serum was collected from a total of 81 PSC patients and 42 healthy controls and tested for reactivity against biliary epithelial cells using flow cytometry. Patient characteristics were correlated with experimental findings. Results. The results showed that a majority of investigated PSC patients had autoreactive IgA against biliary epithelial cells, whereas these antibodies were almost absent in healthy individuals. Presence of autoreactive IgA in the PSC patients was not associated to gender, age, duration of disease, concomitant inflammatory bowel disease, or cholangiocarcinoma. Instead, the levels of autoreactive IgA correlated with higher total serum IgA levels and autoreactive IgA-positive patients progressed faster to a clinical endpoint (death or liver transplantation) compared to autoreactive IgA-negative patients. Conclusions. The findings provide new insights into the role of IgA in PSC patients and opens up for future studies addressing pathogenic mechanisms of autoantibodies directed against biliary epithelial cells.